Optimalisasi Strategi Pemasaran Berbasis Analisis SWOT untuk Peningkatan Penjualan Koperasi Kelompok Usaha Petani Kopi Sridonoretno - Bintang Permata Putri; Tri Yulistyawati Evelina; Eko Boedhi Santoso (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This research is motivated by the needs of Cooperative coffee farmers Sridonoretno Business Group located in the village of Purwosari to improve the effectiveness of marketing strategies in order to increase sales of coffee products produced by its members. Cooperatives as one of the member-based economic institutions require appropriate marketing strategies to be able to compete in an increasingly competitive market, while supporting business sustainability and member welfare. The main purpose of this study is to formulate a marketing strategy in accordance with the conditions and potential of the cooperative. The research method applied is a qualitative approach with data collection through in-depth interviews with three main informants who are considered to have important insights and experience related to cooperative operations and marketing. SWOT analysis is used to identify the strengths, weaknesses, opportunities, and threats facing the cooperative, while the Analytical Hierarchy Process (AHP) method is applied to determine the priorities of marketing strategies based on strategic factors that have been identified. The results showed that the internal conditions of cooperatives strongly support the implementation of aggressive growth policies in marketing, focusing on increasing product distribution, more intensive promotion, and development of superior products. The formulated strategy is expected to be a practical guide for cooperatives to increase competitiveness, expand market share, and maintain business sustainability. However, this study has limitations because it only focuses on marketing aspects, without considering other external factors such as global market conditions, consumer behavior, and government policies that also affect the performance of cooperatives. Therefore, further research is recommended to involve more cooperative members and consumers as informants so that the resulting marketing strategy is more comprehensive, realistic, and applicable in the long term.